BEHAVIOR OF STUDENT CONSUMPTION BIDIKMISI SCHOLARSHIP YEAR 2014-2016 AT FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Indah Sari; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
research was conducted at the Faculty of Social and Political Sciences, University of Riau. The study is titled “Behavior of Student Consumption Bidikmisi Scholarship Year 2014-2016 at Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau”. The purpose of this research is to know the behavior of students in spending or utilizing Bidikmisi scholarship. The focus of this research is the influence of knowledge, perception and motivation of students in using Bidikmisi scholarship at the Faculty of Social and Political Sciences, University of Riau. Samples from this study were 82 people drawn from the population with a 10% error rate. The data that has been collected will be encoded after that the data will be tabulated. The tabulated data will be analyzed and described descriptively quantitatively. Data instruments are observations, questionnaires and documentation.The research conducted found that there are three attitudes of respondents in using bidikmisi scholarship, that is as follows: Set aside or save, Almost all respondents use scholarship budget to save (95,1%). Research conducted found that respondents are aware of the needs of college that could have to be met suddenly. Spending at the beginning of the month, Only a portion of respondents (2.4%) are using a scholarship at the beginning of the month. When conducting the questionnaire, respondents revealed that they spent the scholarship budget at the beginning of the month. Spending by the end of the month, There are some respondents (2.4%) who spend their scholarships by the end of the month. Actually, the respondent may spend at the beginning of the month, but the respondent is reluctant because if it is spent at the end of the month it can be a little guard if there are other necessities that must be met at the beginning and middle of the month. Keywords: Behavior, Consumption, Scholarship, Bidikmisi, Student